Evaluation of farm transportation system in Osun and Oyo states of Nigeria (2005)
An assessment of farm transportation system to ascertain the availability of transportation for the evacuation of farm produce was undertaken in Osun and Oyo states of Nigeria employing printed questionnaires and personal communication as means of information collection. 20% of the farmers reside at between one and three km from their farms while for the remaining 80%, it ranges from four to 16 km. 17.6% of the farmers travel between one and three km to sell their produce while for the remaining 82.4%, the distances range from four to over 16 km. 61.8% of the farmers have access to only untarred roads, 9.1% to partly untarred/tarred roads and only 29.1% get to their farms except for the last stretch through tarred roads. The vehicles found on farm routes in the area surveyed include bicycles, cars, buses, pick-up vans and lorries. 32.7% of farmers and 86.8% of produce merchants don't own any form of transport and hence they depend on commercial transport, which could be scarce and expensive. Road conditions are deplorable especially during the rainy season and this cause further wear and tear on the poor condition vehicles used on the roads and delays in produce delivery. As palliative measures towards ameliorating the situation, it is recommended that roads users associations be formed with the objective of mobilizing men and resources to ensure regular maintenance of the routes. The two states' transport services should be extended to at least those farming areas where the routes are motorable. Non-governmental organizations involved in poverty alleviation programmes such as the Nigerian farmers association and farmers’ development union should provide credit facilities to enable farmers and farmers' groups acquire farm transport vehicles while the activities of the federal road maintenance agency should be extended to the food basket areas.